Kānwičhai læ phatthanā kānsongsœ̄m sukkhaphāp nai radap rāk yā phư̄a sāng khwāmkhēmkhǣng khō̜ng chumchon karanī sưksā : phư̄nthī čhangwat Nakhō̜n Sawan ʻUthai Thānī læ Chai Nāt - Čhētsadā Thanawiphākhanon (Khana Kharusāt, Mahāwitthayālai Rātchaphat Nakhō̜n Sawan, 2007)
Research report on the development project on health promotion for strengthening the grass-root communities in Thailand, case study of Nakhon Sawan, Uthai Thani and Chai Nat provinces, Central Region.